Drug resistance against 5-fluorouracil and cisplatin in the treatment of head and neck squamous cell carcinoma: A systematic review - Fatemeh Atashi; Nafiseh Vahed; Parya Emamverdizadeh; Shirin Fattahi; Ladan Paya (Tabriz University of Medical Sciences, 2021)
Head and neck cancers are highly prevalent worldwide. Most of these lesions are diagnosed in the advanced stages of the disease. Thus, they do not often have a good long-term prognosis. Like other cancer types, head and neck cancers are managed by surgery, radiotherapy, and chemotherapy. Despite significant advances in the treatment of oral squamous cell carcinoma (OSCC), physicians encounter several challenges in the course of treatment. Various mechanisms mediate the clinical responses of a certain cancer to medications. Thus, efficient treatment planning requires adequate knowledge about the genes involved in drug resistance and the evaluation of the frequency percentage of resistance. Several studies have evaluated the causes and frequency percentages of 5-fluorouracil (5-FU) and cisplatin resistance. In this systematic review, all the relevant articles published until November 30, 2019, were retrieved from the Scopus, Embase, Medline, ISI, Web of Science, and Cochrane databases using certain MeSH and EMTTree keywords. A total of 2164 articles were retrieved of which, 18 were included in the review since they had reported the frequency percentages of drug resistance. Of all, 10 articles had evaluated cisplatin (1317 samples). A meta-analysis of the results revealed a frequency of 33% for cisplatin resistance. Eight studies had evaluated 5-FU (476 samples). A meta-analysis of the results revealed a frequency of 40.2 % for 5-FU resistance. Overcoming cisplatin resistance or 5-FU resistance can significantly enhance recovery in advanced HNSCC. Attempts should be made to eliminate the cause and use multi-drug regimens to increase the success rate of treatment.